DNA fingerprinting of human isolates of salmonella enterica serotype paratyphi B in Malaysia - Goh, Y.L.; Yasin, R.; Puthucheary, S.D.; Koh, Y.T.; Lim, V.K.E.; Taib, Z.; Thong, Kwai Lin (Wiley, 2003)
Aims: DNA fingerprinting of Salmonella enterica serotype Paratyphi B isolated in Malaysia during 1982-83, 1992 and 1996-2002 was carried out by pulsed-field gel electrophoresis (PFGE), antimicrobial susceptibility tests and D-tartrate utilization tests to assess the extent of genetic diversity of these isolates in Malaysia. Methods and Results: Eighty-six human isolates and one food isolate of Salm. Paratyphi B were analysed by PFGE, antimicrobial susceptibility tests and D-tartrate utilization tests. Sixty-five strains were d-tartrate-negative (dT-) while 22 strains were D-tartrate-positive (dT+). Thirty-seven per cent of the Salm. Paratyphi B strains were resistant to one or more antimicrobial agents. PFGE analysis clearly distinguished the dT- and dT+ strains into two clusters based on the unweighted pair group average method (UPGMA). Twenty-two XbaI-pulsotypes were observed among the 65 dT- strains while 17 XbaI-pulsotypes were observed among the 22 isolates of Salm. Paratyphi B dT+. Conclusions: The present study showed that PFGE was very discriminative with 33.7 of the strains yielding distinct fingerprints. Paratyphoid fever in Malaysia is probably caused by one predominant, endemic clone of Salm. Paratyphi B dT- with various subtypes. There was no association between the pulsotypes and the severity of the disease indicating that the severity of the disease is probably multifactorial. Significance and Impact of the Study: The findings of the present study verify the usefulness of PFGE in characterizing strains of Salm. Paratyphi B. This is the first report on the application of PFGE on a large collection of Salm. Paratyphi B in Malaysia.